Functional insights into modulation of BKCa channel activity to alter myometrial contractility - Lorca, Ramón A.; Prabagaran, Monali; England, Sarah K. (Frontiers in Physiology, 2014)
The large-conductance voltage- and Ca2+-activated K+ channel (BKCa) is an important regulator of membrane excitability in a wide variety of cells and tissues. In myometrial smooth muscle, activation of BKCa plays essential roles in buffering contractility to maintain uterine quiescence during pregnancy and in the transition to a more contractile state at the onset of labor. Multiple mechanisms of modulation have been described to alter BKCa channel activity, expression, and cellular localization. In the myometrium, BKCa is regulated by alternative splicing, protein targeting to the plasma membrane, compartmentation in membrane microdomains, and posttranslational modifications. In addition, interaction with auxiliary proteins (i.e., β1- and β2-subunits), association with G-protein coupled receptor signaling pathways, such as those activated by adrenergic and oxytocin receptors, and hormonal regulation provide further mechanisms of variable modulation of BKCa channel function in myometrial smooth muscle. Here, we provide an overview of these mechanisms of BKCa channel modulation and provide a context for them in relation to myometrial function.